INTEGRATING EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) IN HIGHER EDUCATION INSTITUTIONS TO REDUCE THE IMPACT OF CLIMATE CHANGE ON AGRICULTURAL INDUSTRIES - Dodhy Hyronimus Ama longgy; Tini Adiatma; Simon Siamsa (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Education for sustainable development (ESD) became a highlighted issue in the educational sector all around the world. The concept is to integrate the social, economic, and environmental aspects to create a more comprehensive solution to maintain planet sustainability. Higher education as an institution that creates agents of change in society must be adapted toward nowadays issues that are related to global development. Agricultural industries became an area that was also impacted by climate change. Higher education is an institution that also undertakes tri dharma that carries on their solution toward this issue. This research aims to explore how to integrate of Education for Sustainable Development in higher education institutions (HEI) to reduce the impact of climate change on agricultural industries. The research uses a systemic literature review related to the topic. This research result is a strategy to integrate Education for Sustainable Development (ESD) in higher education starting by making a commitment, program planning, and integrating into the curriculum to improve the university student’s awareness about the impact of climate change on food security and planet sustainability. Higher education can make a broad effect on agricultural mitigation of climate change. This program can be implemented in a higher education institution to make a more relevant learning process that also supports “Merdeka Belajar” curriculum in Indonesia.